Kemotaksonomi dan Farmakologi Tumbuhan Keluarga Guttiferae - Syamsudin Syamsudin (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
The Guttiferae family has many species with interesting phytochemical properties. Is has been widely used in the traditional medicine and contains xanthones as constituent, exhibiting biological and pharmacological activities for example, e. g. as antimalaria, antimicrobe, antioxidant, anticancer and HIV-1 protease inhibitor.